1994
DOI: 10.1061/(asce)0733-9410(1994)120:12(2155)
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Response of Soil‐Wall Systems

Abstract: Thisreport was preparedasan accountofwork sponsoredby an agencyoftheUnited StatesGovernment. Neither the UnitedStatesGovernment nor any agency thereof, nor any of theiremployees,nor any of theircontractors, subcontractors, or their employees, makes any warranty,express orimplied, orassumes any legal liability or responsibility forthe accuracy,completeness, or usefulness of any information, apparatus, product, orprocess disclosed, orrepresents thatitsusewould notinfringe I privately owned rights. Reference here… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
4

Year Published

1995
1995
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 11 publications
2
42
0
4
Order By: Relevance
“…For example, Wood [13] and Veletsos and Younan [23] formulated solutions for the seismic increment of lateral earth pressure exerted by a soil deposit with a parabolic variation of shear modulus with depth, G(z). Rovithis et al [24] suggest a form for shear wave velocity as a function of depth, Vs(z), that is equivalent to the equation for G(z) in Eq.…”
Section: Vertical Variation Of Soil Shear Modulusmentioning
confidence: 99%
“…For example, Wood [13] and Veletsos and Younan [23] formulated solutions for the seismic increment of lateral earth pressure exerted by a soil deposit with a parabolic variation of shear modulus with depth, G(z). Rovithis et al [24] suggest a form for shear wave velocity as a function of depth, Vs(z), that is equivalent to the equation for G(z) in Eq.…”
Section: Vertical Variation Of Soil Shear Modulusmentioning
confidence: 99%
“…Apart from some numerical solutions (Psarropoulos et al, 2005;Ling et al, 2005;Callisto and Soccodato, 2010), the analytical methods have been highlighted for the closed-form property, such as the early representative solutions (Matsuo and Ohara, 1960;Wood, 1973Wood, , 1975Arias et al, 1981;Scott, 1973). It has been shown that Veletsos and Younan (1994a, 1994b, 1997; Younan and Veletsos (2000) made use of Lagrange's equations of motion and presented a series of complete accurate elastic models for dynamic responses of the rigid and flexible walls by vanishing vertical stresses of the soil-wall system. Wu and Finn (1999) presented a plane strain elastic solution for the problem by neglecting vertical displacements.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the models of Veletsos and Younan (1994a, 1994b, 1997; Younan and Veletsos (2000) have been extended to the cases of different constrained conditions of the wall (Jung et al, 2010) and the poroelastic medium (Theodorakopoulos et al, 2001a(Theodorakopoulos et al, , 2001bTheodorakopoulos, 2003;Theodorakopoulos and Beskos, 2003;Lanzoni et al, 2007). The direct analytical solutions by Veletsos and Younan (1994a, 1994b, 1997; Younan and Veletsos (2000) are powerful and useful, but they are a little complicated (Theodorakopoulos et al, 2001b). The author proposed an analytical solution based on a modified Vlasov-Leontiev foundation model by vanishing vertical displacements with an iterative procedure (Liu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, one can mention here Mononobe and Matsuo [6], Okabe [7] and Seed and Whitman [8] from the first category, Wood [9], Veletsos and Younan [10,11], Papazafeiropoulos and Psarropoulos [12] and Brandenberg et al [13] from the second category and Wu and Finn [14], Al Atik and Sitar [15], and Wilson and Elgamal [16] from the third category.…”
Section: Introductionmentioning
confidence: 99%
“…The more usual case of one retaining wall can be obtained here as a special case of the two walls system by taking the distance between the two walls to be very large. The seismic problems of one or a pair of rigid walls retaining poroelastic soil have been solved by Theodorakopoulos et al [17][18][19][20] and Theodorakopoulos [21] in an approximate analytical manner by following the methodology of Veletsos and Younan [10,11] used for the case of elastic soil. Following the same approximations as in [10,11], Lanzoni et al [22] were able to solve analytically the problem of the seismic response of a flexible cantilever wall retaining poroelastic soil.…”
Section: Introductionmentioning
confidence: 99%